PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN MIGAS DI BURSA EFEK INDONESIA PERIODE 2016–2020) - Muh. Akbar Muktadirun; Buyung Sarita; Sujono Sujono; Riski Amalia Madi (Jurnal Manajemen dan Kewirausahaan, 2022)
This study aims to determine the Effect of Fundamental Factors on Stock Prices (Study on Oil and Gas Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016–2020 Period). The population of this study is the oil and gas mining sub-sector companies, totaling 9 companies. The sample was determined using purposive sampling method, to get a sample of 7 companies. The analytical method used is panel data regression analysis and processed using the Eviews 9 application. Based on the results of the study, it shows that Earning Per Share (EPS), Price to Earning Ratio (PER) and Company Size have a positive and significant effect on stock prices. Meanwhile, Net Profit Margin (NPM) and Debt to Equity Ratio (DER) have a positive and insignificant effect on stock prices. On the other hand, Return On Equity (ROE) has a negative and insignificant effect.